Use of Interactive Whiteboards in ELT - Černá, Kristýna (Univerzita Pardubice, 2014)
This bachelor thesis deals with the use of interactive whiteboards in English language teaching. The work is divided into two main parts. The theoretical part introduces an interactive whiteboard, classifies it and briefly describes its development. Reasons for the use of interactive whiteboards in English lessons are described in the upcoming chapter of the work. The theoretical part concludes with the introduction of selected factors that are influenced by integration of interactive whiteboard into the teaching process. In the practical part, the real situation of using interactive whiteboards in English lessons is mapped with the use of observations and questionnaires.
Použití interaktivní bílé tabule ve výuce anglického jazyka
Keywords: výuka anglického jazyka; interaktivní tabule; informační a komunikační technologie; vyučovací procesy; role učitele; English language teaching; interactive whiteboards; information and communication technologies; teaching processes; roles of the teacher